The effects of students’ perception on self-efficacy in programming courses at the tertiary institution - Isaac Ampofo Atta Senior (Ukrainian Journal of Educational Studies and Information Technology, 2023)
Programming is a difficult subject to learn and teach. When it comes to students learning basic programming information and skills, university-level introductory programming courses (Java, C++, Visual Basic, and Python) are critical. Students' achievement is negatively impacted by a negative attitude about programming. As a result, the study discovered the impact of students' perceptions in university computer programming courses. The study covered students studying Computer Science from the University of Ghana. A survey descriptive design with a quantitative technique was used in this investigation. The population of the study was 2,030 with 368 sample size. Purposive sampling was utilized to choose University of Ghana, Legon as the study's location. The study's participants were chosen using a stratified random sampling technique. Closed-ended questionnaire was used for data collection. The SPSS version 26 and PROCESS Macro were used to analyze the data. Respondents’ data were examined applying both inferential and descriptive statistics. The study revealed that students see programming as unfamiliar was the highest perception of programming to students. The study found that students see programming as easy with dedication was the lowest perception of programming to students. In conclusion, the significant impact of perception of students in Computer Programming account for 84% of the contribution of factors that influence self-efficacy.